Impact of plasma jet geometry on residence times of radical species - Lalor, James; Scally, Laurence; Cullen, Patrick J.; Milosavljević, Vladimir (AIP Publishing, 2018)
Numerous electrode geometries and power supplies, both commercial and in-house, have been employed for the generation of low-temperature atmospheric plasma jets. In this work, the development and operation of a 12 jet nonthermal atmospheric plasma system is presented. The study is based on optical spectroscopy as a diagnostic method due to its nonintrusive nature. A key focus of this study was the material selection (conductive and nonconductive), with several polymers screened for the jet design leading to polyacetal as the choice material. Their results are compared with other atmospheric plasma jet systems. The results show a significant increase in residence time and the spatial homogeneity for ambient air's main species, including: OH, O I, O2, O3, N2, and N2+. Their densities are studied with respect to treatment time, distance, duty cycle, and discharge frequency, as well as the jets' carrier gas chemistries (argon and helium). For their plasma jet system, the bulk of the chemical reactions occur in the surrounding atmosphere and not in the jet nozzle, which is different from most other plasma jet systems. The electron energy distribution function, for the given chemistries, is also reported